Self-Awareness and Self-Reflection on the Counselor's Personal Development - Neni Aprilia; Nasyiwa Ramadhin; Tri Wulandari; Asbi Asbi (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
By reviewing the literature thoroughly, this study investigates how self-awareness and self-reflection contribute to counselors' personal growth. Two important components, self-awareness and self-reflection, were identified as positively correlated with counseling effectiveness and client satisfaction. Self-awareness helps counselors manage counter-transference and differentiate personal problems from client problems, while self-reflection improves empathy skills and bridges theory with practice. This study shows that both components must be included in the experiential learning cycle and that a person must be in an environment that supports self-exploration. Challenges in this process include psychological discomfort and non-linear developmental patterns. The implication is that counselor education programs need to place greater emphasis on developing self-awareness and reflection skills, including the integration of personal therapy in training. It was concluded that self-awareness and self-reflection are components that lead counselors toward continued professional growth, resulting in not only technical skills but also wisdom in navigating the complexities of the therapeutic relationship.